2011
DOI: 10.1111/j.1365-2923.2011.04056.x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-based assessments of junior doctors: do scores predict training difficulties?

Abstract: Medical Education 2011: 45: 1190–1198 Objectives  Workplace‐based assessment (WPBA) is an increasingly important part of postgraduate medical training and its results may be used as evidence of professional competence. This study evaluates the ability of WPBA to distinguish UK Foundation Programme (FP) doctors with training difficulties and its effectiveness as a surrogate marker for deficiencies in professional competence. Methods  We conducted a retrospective observational study using anonymised records for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 15 publications
1
60
0
Order By: Relevance
“…The relationship between the tool's content and the construct measured (content validity) was not evaluated in any of the studies. Three of the included articles examined the relationship of the assessment tool to other variables (Mitchell et al 2011;Brittlebank et al 2013;Eardley et al 2013). Mitchell et al (2011) concluded a significant association between the average score and training difficulties of all types (OR ¼ 3.9, 95% confidence interval [CI] ¼ 0.21-0.72).…”
Section: Evidence Of Validitymentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between the tool's content and the construct measured (content validity) was not evaluated in any of the studies. Three of the included articles examined the relationship of the assessment tool to other variables (Mitchell et al 2011;Brittlebank et al 2013;Eardley et al 2013). Mitchell et al (2011) concluded a significant association between the average score and training difficulties of all types (OR ¼ 3.9, 95% confidence interval [CI] ¼ 0.21-0.72).…”
Section: Evidence Of Validitymentioning
confidence: 99%
“…Three of the included articles examined the relationship of the assessment tool to other variables (Mitchell et al 2011;Brittlebank et al 2013;Eardley et al 2013). Mitchell et al (2011) concluded a significant association between the average score and training difficulties of all types (OR ¼ 3.9, 95% confidence interval [CI] ¼ 0.21-0.72). Eardley et al (2013) found no evident relation between the stage of training and the summary rating given.…”
Section: Evidence Of Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…1 Learner assessment in this approach generates rich narrative descriptions of the behaviors of a competent professional, which are used to determine progress and achievement toward these goals. The development of workplace-based assessments (WBAs) that are reliable, valid, feasible, educationally useful, and acceptable to faculty raters is critical to making these complex judgments.…”
Section: Introductionmentioning
confidence: 99%